Polska literatura obozowa. Kilka pytań o syntezę, której nie ma - Kulesza, Dariusz (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2018)
The author of the paper wonders why nobody so far has attempted a historical-literary synthesis of Polish literature concerning the concentration camp experience in general, and the labour camp experience in particular, as the latter has an obvious potential for a proto-synthesis. The question is followed by subjective answers that build upon the significance of Tadeusz Borowski’s prose, the uniqueness of the Holocaust, and differences between the records of the camp experience in Poland and abroad. In its central part, the paper points to a certain possibility at our disposal to – irrespective of almost insurmountable obstacles – at least start the aforementioned synthesis. This can be done by the application of the external criteria: historical-geographical (what camps, when and where) and historical-literary, which would include such perspectives and categories as periodization, literary genres and comparative studies.